Mapping social work education in the West Africa region: Movements toward indigenization in 12 countries' training programs. (6th January 2019) - Canavera, Mark; Akesson, Bree; Landis, Debbie; Armstrong, Miranda; Meyer, Elizabeth
Abstract : This article presents the results of a systematic mapping of social work training programs in countries throughout West Africa, a region historically under‐represented in global discussions of the social welfare workforce. The research illuminates how social workers and related professionals are trained to engage in social work practice in a number of West African countries. The research was conducted in two phases. In the initial phase, the research team collected documents from 12 West African countries and conducted phone interviews with relevant individuals. The second phase included field research in five West African countries − Burkina Faso, Côte d'Ivoire, Ghana, Nigeria, and Senegal − where the research team conducted semi‐structured interviews and group discussions with 253 individuals. Framed by indigenization theory, this study describes social service training institutes in West Africa and highlights the varying degrees to which programs have been adapted to indigenous and endogenous realities in the postcolonial era.